2011
DOI: 10.1007/s11224-011-9834-8
|View full text |Cite
|
Sign up to set email alerts
|

Analogy between sulfuryl and phosphino groups: the aromaticity of thiophene-oxide

Abstract: Sulfur in thiophene-oxide is pyramidal, thus this heterocycle shows structural similarities with phosphole. The aromaticity measures (e.g., ISE c = 1.1 kcal/mol; NICS(0) = -5.2) are also comparable (for phosphole ISE c = -2.7 kcal/mol; NICS(0) = -5.4) indicating a borderline non-aromatic/slightly aromatic behavior. The extent of aromaticity is also similar-and high-for the planar transition structures of the inversion motion (thiopheneoxide: ISE c = -20.4 kcal/mol; NICS(0) = -18.7 and phosphole ISE c = -17.7 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 63 publications
1
3
1
Order By: Relevance
“…Aromaticity Before investigating the extended systems, the aromaticity of the parent rings (Table 1) has been calculated at the highest used level of theory (B3LYP/cc-pVTZ). The results (summarized in Table 1) are in good agreement with the values published previously at a somewhat different level of theory [42]. As expected, NICS(1) values span a wide range between -10.7 for tiophene, a highly aromatic ring and +11.6 for antiaromatic borole.…”
Section: Resultssupporting
confidence: 90%
“…Aromaticity Before investigating the extended systems, the aromaticity of the parent rings (Table 1) has been calculated at the highest used level of theory (B3LYP/cc-pVTZ). The results (summarized in Table 1) are in good agreement with the values published previously at a somewhat different level of theory [42]. As expected, NICS(1) values span a wide range between -10.7 for tiophene, a highly aromatic ring and +11.6 for antiaromatic borole.…”
Section: Resultssupporting
confidence: 90%
“…Computed results given in Table show that all compounds considered are aromatic systems with negative NICS values. Previous reports showed that the aromaticity of furan is slightly reduced as compared to those of thiophene and selene. , However, our predictions in this context reveal an opposite trend. The NICS values obtained at the center of furan are systemically more negative than those obtained at the centers of thiophene and selene.…”
Section: Resultscontrasting
confidence: 77%
“…NICS values [22] are collected in Ta ble S7, and are presentedi nF igure 6, in which the size of the circles is proportionalt ot he NICS(1) value, black represents antiaromatic, whereas gray denotes aromatic ring current (NICS(0) shows as imilar behavior,s ee Figure S13). It is known that phosphole-sulfides are slightly antiaromatic [23] (in general,o xidation of second row heteroatoms such as phosphoruso rs ulfur decreases the aromaticity), [24] and accordingly the five-membered rings are antiaromatic for the entire series. More interestingly, the endocyclics ix-membered ring fused with the five-membered ring also becamea ntiaromatic, throughout the entire series!W ith the increasinge xtent of the conjugation,t he antiaromaticity shows some increaset hroughout the series 2a S -3a S -4a S ,a lthough the values remain small; for example, in case of NICS(1), the value for the endocyclic six-membered ring is + 3.0.…”
Section: Theoretical Calculationsmentioning
confidence: 99%